Improving “quality of life” through exercise and proper nutrition - Bellomo, Rosa Grazia; Saggini, Raoul; Barbato, Claudia (Journal of Sports Medicine and Therapy, 2022)
In line with what is defined by W.H.O. (World Health Organization) the objective of the work is to observe and define the interconnection between a healthy lifestyle and the quality of life perceived by people. For this purpose, 30 healthy subjects, who had never practiced sports at a competitive level, were recruited. All individuals were evaluated at T0 and T1 through clinical evaluation and specific functional tests to define the psycho-physical well-being of the person. For three months they were followed with a personalized diet. Subjects were divided into two randomized groups: group A called experimental that followed the protocol for the duration of the study, and group B said evaluation group that performed only evaluations at the same time as group A. both groups were evaluated twice, the first immediately after the last training session, the second evaluation was performed after 30 days from the first. The objective of the project was to analyze, after three months, the cognitive changes in memory and concentration skills, stress experienced at work or study, and psycho-physical well-being perceived by interested parties. The data collected during the evaluations showed that the interconnection between a healthy lifestyle and the quality of life perceived by people is evident.